Partial Substitution of Asphalt Concrete Filler with Eco-Friendly Burnt Sawdust - Mohamed Lakhder Guesmi; Zahreddine Nafa; Abdelhak Bordjiba; Faouzi Bouras (The Journal of Engineering and Exact Sciences)
This paper investigates the effects of burnt sawdust as an additive in asphaltic concrete, aiming to enhance the material's properties. The study sourced redwood sawdust from a carpentry workshop in Djelfa state, Algeria, and obtained bitumen, coarse aggregates, fine aggregates, and mineral filler from the Public Works Laboratory for the South in Ghardaïa state, Algeria. The sawdust was burned at 200°C in a furnace, cooled, and sieved through an 80 µm sieve. Standard procedures were employed to determine the material properties. Asphaltic concrete samples were then prepared with burnt sawdust at varying weight percentages of 0, 5, 15, 20, and 25% of the filler. The Marshall Stability test was conducted to assess the mixtures' stability, flow, density, voids filled with bitumen (VFB), air voids (AV), and voids in mineral aggregate (VMA). The results indicated an optimal sawdust content of 15%, showcasing improved properties when burnt sawdust was added to asphaltic concrete. Additionally, this utilization of sawdust contributes to preserving nonrenewable materials and reduces pollution from mineral filler manufacturing. Furthermore, the use of fine sawdust, typically considered waste, proves an environmentally responsible alternative to disposal.